Suppose $f''(x)\lt0$ for $x\gt0$ , $f(0)=0$ . Prove $$f(x_1)+f(x_2)\gt f(x_1+x_2)$$ for all $x_1\gt0$ and $x_2\gt0$ .

Trying to perform Mean value Theorem, also considered the properties of convex up function. Still have no clue. Especially the condition $f(0)=0$, I don't how to use it .

  • 2
    $\begingroup$ For a fixed $x_2>0$ define $g(x)=f(x)+f(x_2)-f(x+x_2)$. Then show $g(0)=0$ and $g'(x)>0$ to conclude that $g$ stays positive. $\endgroup$ – Marco Aug 30 '18 at 15:19
  • $\begingroup$ More generally you could try to prove $f(x_1+x_2)-f(x_1) \lt f(x_2)-f(0)$ which almost says that the slope between $(x_1,f(x_1))$ and $(x_1+x_2,f(x_1+x_2))$ is less than between $(0,f(0))$ and $(x_2,f(x_2))$ something that is intuitively obvious if $f''(x)<0$. Setting $f(0)=0$ allows you to make $f(0)$ disappear so you can rearrange to $f(x_1)+f(x_2) > f(x_1+x_2)$ $\endgroup$ – Henry Aug 30 '18 at 15:28

Based on what Marco said: For a fixed $x_2>0$ define $g(x)=f(x)+f(x_2)−f(x+x_2)$.

Then $g(0)=f(0)+f(x_2)-f(0+x_2)=0+f(x_2)-f(x_2)=0$

and $\large{g′(x)\\=\mathop{lim}\limits_{h→0}\frac{g(x+h)-g(x)}{h}\\=\mathop{lim}\limits_{h→0}\frac{f(x+h)+f(x_2)−f(x+h+x_2)-f(x)-f(x_2)+f(x+x_2)}{h}\\=\mathop{lim}\limits_{h→0}\frac{[f(x+h)-f(x)]−[f(x+h+x_2)-f(x+x_2)]}{h}\\=\mathop{lim}\limits_{h→0}\frac{f(x+h)-f(x)}{h}-\mathop{lim}\limits_{h→0}\frac{f(x+h+x_2)-f(x+x_2)}{h}\\=f'(x)-f'(x+x_2)>0} $

This is because $f''<0$ gives us that $f'(a)>f'(b)$ for $0<a<b$.



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.